Online and Distance Learning during Lockdown Times COVID-19 Stories (Volume 2) - Edirisingha, Palitha (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a reprint of papers in the Special Issue published in Education Sciences under the title "Online and Distance Learning during Lockdown Times: COVID-19 Stories". It includes papers covering Higher Education (post-secondary) sector representing international experience of teaching and learning from the start of the first episode of lockdown due to the Covid-19 pandemic.